Comparison of Synovex-S and STEER-oid implants for feedlot steers - Lee, B.; Laudert, S. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Synovex-S and STEER-oid were compared in a 133-day finishing trial to evaluate their effects on growth and carcass traits of yearling steers. No significant differences in average daily gain, feed intake, feed to gain ratio, carcass weight, ribeye area, fat thickness, quality grade or yield grade were detected between the two implants at the end of the trial. However, significant differences in feed efficiency were detected during days 0-35 and 36-63, possibly due to different release rates of the implants.
Keywords: Beef; Implants; Steers; Growth; Carcass traits; Quality grade; Yield grade